Mosby's physical examination DVD series [ DVD12, Male genitalia, rectum and prostate - Ball, Jane; Benedict, G. William; Dains, Joyce E.; Seidel, Henry M. (Mosby Elsevier, 2006)
This 10 minute video shows the steps needed to examine the male genitalia, rectum, and prostate, including the proper use of equipment. With the patient standing, it demonstrates how to inspect and palpate the patient's external genitalia and assess for hernias. Then with the patient leaning over the examination table, it presents inspection and palpation of the prostate, anus, and rectum, including bidigital examination. The video shows expected findings and highlights selected variations in techniques and expectations for pediatric and geriatric patients. In addition, it uses graphics to reveal what is happening internally during examination of the rectum and prostate."--Publisher's website